KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN PROFESIONALISME GURU - Fatra, Fatra; Rochyani, Neny (Jurnal Dosen Universitas PGRI Palembang)
Abstract: Teachers, as a major resource in improving the quality of professional education required. With an awareness of professional responsibility that is owned, every teacher is expected to constantly push himself to provide the best in education for students. Professional awareness as the educators who must carry out their profession in total and wholehearted must continue to be built within the teacher. The problems that occur in connection with the need to increase the professionalism of teachers to teach in school relate to: the lack of motivation of teachers to develop their professional ability, lack of facilities and infrastructure, as well as the intensity increases each time less. The purpose of this is to find out enelitian principals role in developing the professionalism of teachers. In this study, researchers delve deeply into the role of school leadership SMA Muhammadiyah 1 Palembang in developing the professionalism of teachers. Principal support is very important to encourage teachers to improve teaching. One of the principals do is provide financial intensive for teachers efforts to improve the teaching, such as the development of teaching materials. Principal support the desire of teachers to continue their education to S2. Noting the need for teachers welfare is a part that is not less important to improve the professionalism of teachers.Keywords: Leadership, Headmaster, Teacherâs Professional